Pengaruh Suhu Dan Lama Pengeringan Terhadap Karakteristik Teh Celup Herbal Daun Gonda (Sphenoclea zeylanica Gaertn.) - Audi Simbolon, Christofer; Yusa, Ni Made; Kencana Putra, Nengah (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 3 (2023): Jurnal ITEPA, 2023)
This study aims to determine the effect of temperature and proper drying time to produce gonda leaf herbal tea bags with the best characteristics. This research used a completely randomized factorial design with two factors, namely drying temperature (50oC, 60oC, 70oC) and drying time (180 minutes, 210 minutes, 240 minutes). There are 9 treatment combinations, each treatment combination is repeated 2 times so that the number of treatment combinations is 18 experimental units. The data obtained were analyzed by analysis of variance. If the treatment had a significant effect, it would be followed by the Duncan test. The results showed that interaction beetwen drying temperature and time treatment had a very significant effect (P<0,01) on moisture content, total phenolic content, antioxidant activity and hedonic taste of gonda leaf herbal tea, have a significant effect (P<0,05) on total flavonoid content and hedonic colour and also had no significant effect (P>0, 05) to test the hedonic aroma and overall acceptance. The drying temperature of 50oC with a drying time of 240 minutes was the best temperature and drying time to produce herbal tea bags of gonda leaves with an antioxidant activity of 58.56% with IC50 1136443,36 ppm, moisture content of 6.37%, total phenolic content was 5.07 mg GAE / g, total flavonoid content was 0.84 mg QE / g, and sensory properties of colour 3.45 (slight liked), aroma 3.15 (neither like nor dislike), taste 3,65 (liked) and overall acceptance 3.15 (neither like nor dislike).